1989
DOI: 10.1128/jb.171.4.2075-2082.1989
|View full text |Cite
|
Sign up to set email alerts
|

Release of flagellar filament-hook-rod complex by a Salmonella typhimurium mutant defective in the M ring of the basal body

Abstract: A Salmonella typhimurium strain possessing a mutation in thefliF gene (coding for the component protein of the M ring of the flageilar basal body) swarmed poorly on a semisolid plate. However, cells grown in liquid medium swam normally and did not show any differences from wild-type cells in terms of swimming speed or tumbling frequency. When mutant cells were grown in a viscous medium, detached bundles of flagellar ifiaments as long as 100 ,um were formed and the cells had impaired motility. Electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 26 publications
2
40
0
Order By: Relevance
“…Purification and amino acid analysis of the B. subtilis hook Because the flagellar filaments are external to the cell, they tend to detach from the cell body by shear force, leaving the flagellar basal body in the membrane, as shown for S. typhimurium (Okino et al, 1989). This is also true for B. subtilis: pipetting the cell suspension effectively shears off most of the filaments.…”
Section: Resultsmentioning
confidence: 99%
“…Purification and amino acid analysis of the B. subtilis hook Because the flagellar filaments are external to the cell, they tend to detach from the cell body by shear force, leaving the flagellar basal body in the membrane, as shown for S. typhimurium (Okino et al, 1989). This is also true for B. subtilis: pipetting the cell suspension effectively shears off most of the filaments.…”
Section: Resultsmentioning
confidence: 99%
“…propagated over considerable distances, since the length of the rod exceeds the direct reach of the P ring, which is located in the vicinity of the junction between the FlgG portion and the proximal portion (39,44). Independent evidence for propagated effects in the rod comes from a mutant whose rod is prone to shear at the junction between the proximal and distal zones (39), yet whose defect lies in the M-ring protein, which is located about 20 nm away.…”
mentioning
confidence: 99%
“…Independent evidence for propagated effects in the rod comes from a mutant whose rod is prone to shear at the junction between the proximal and distal zones (39), yet whose defect lies in the M-ring protein, which is located about 20 nm away.…”
mentioning
confidence: 99%
“…Okino et al (5) observed that highly viscous medium destabilizes the flagella of Salmonella typhimurium. They analyzed a particular mutant strain that swims well in liquid, but loses its flagella in semi-solid agar or liquid media with high viscosity.…”
Section: Discussionmentioning
confidence: 99%